Influenza A virus infection instructs hematopoiesis to megakaryocyte-lineage output - Rommel, Marcel G. E.; Walz, Lisa; Fotopoulou, Foteini; Kohlscheen, Saskia; Schenk, Franziska; Miskey, Csaba; Botezatu, Lacramioara; Krebs, Yvonne; Voelker, Iris M.; Wittwer, Kevin; Holland-Letz, Tim; Ivics, Zoltán; et al. (Cell reports, 2022)
Respiratory tract infections are among the deadliest communicable diseases worldwide. Severe cases of viral lung infections are often associated with a cytokine storm and alternating platelet numbers. We report that hematopoietic stem and progenitor cells (HSPCs) sense a non-systemic influenza A virus (IAV) infection via inflammatory cytokines. Irrespective of antiviral treatment or vaccination, at a certain threshold of IAV titer in the lung, CD41-positive hematopoietic stem cells (HSCs) enter the cell cycle while endothelial protein C receptor-positive CD41-negative HSCs remain quiescent. Active CD41-positive HSCs represent the source of megakaryocytes, while their multi-lineage reconstitution potential is reduced. This emergency megakaryopoiesis is thrombopoietin independent and attenuated in IAV-infected interleukin-1 receptor-deficient mice. Newly produced platelets during IAV infection are immature and hyper-reactive. After viral clearance, HSC quiescence is re-established. Our study reveals that non-systemic viral respiratory infection has an acute impact on HSCs via inflammatory cytokines to counteract IAV-induced thrombocytopenia.
Gesehen am 26.10.2022